2007
DOI: 10.5194/acp-7-5175-2007
|View full text |Cite
|
Sign up to set email alerts
|

The Tropical Forest and Fire Emissions Experiment: overview and airborne fire emission factor measurements

Abstract: Abstract. The Tropical Forest and Fire Emissions Experiment (TROFFEE) used laboratory measurements followed by airborne and ground based field campaigns during the 2004 Amazon dry season to quantify the emissions from pristine tropical forest and several plantations as well as the emissions, fuel consumption, and fire ecology of tropical deforestation fires. The airborne campaign used an Embraer 110B aircraft outfitted with whole air sampling in canisters, mass-calibrated nephelometry, ozone by UV absorbance, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
245
6
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(274 citation statements)
references
References 68 publications
22
245
6
1
Order By: Relevance
“…This analysis rests on several assumptions: (1) that the study-average mix of fire emissions we sampled resembled the real, average fire-emissions mix -on the days of the downwind measurements, (2) that other types of biomass burning in the study area may be ignored, and (3) that our airborne measurements of the fire ER HCN/CO are also valid for any initially-unlofted smoldering fire emissions . The third assumption is supported by the fact that EFHCN are not strongly dependent on MCE in this work (or in Africa or Brazil (Yokelson et al, 2007)). …”
Section: Preliminary Assessment Of the Contribution Of Fires To The Msupporting
confidence: 56%
“…This analysis rests on several assumptions: (1) that the study-average mix of fire emissions we sampled resembled the real, average fire-emissions mix -on the days of the downwind measurements, (2) that other types of biomass burning in the study area may be ignored, and (3) that our airborne measurements of the fire ER HCN/CO are also valid for any initially-unlofted smoldering fire emissions . The third assumption is supported by the fact that EFHCN are not strongly dependent on MCE in this work (or in Africa or Brazil (Yokelson et al, 2007)). …”
Section: Preliminary Assessment Of the Contribution Of Fires To The Msupporting
confidence: 56%
“…Some studies have shown that emission factors (EF) for ground-based measurements of smoldering compounds were higher than the EF measured for the same compounds from an aircraft above the same fires. This could be due to weakly lofted smoldering emissions collected by flight measurements, as occurred in the Babbitt et al [40] study, for example [23]. This fact could result in higher values for smoldering compounds from laboratory and field measurements.…”
Section: Resultsmentioning
confidence: 88%
“…Some limitations of the available measurements are mentioned as follows. Flight measurements such as the Le Canut et al [34] study in Africa tend to sample emissions that are associated with more intense and flaming combustion [23,24]. On the other hand, laboratory measurements could provide higher emission factors (EF) in relation to the previous method and be influenced by some factors as well as the types of instruments and calibrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yokelson et al (1997) measured the emission from the smoldering combustion of biomass with a Fourier transform infrared spectrometer (FT-IR) coupled to an open multipass cell. Numerous field campaigns have also been conducted in an effort to quantify and characterize emissions from biomass burning from different ecosystems such as the the work done by Yokelson et al (2003) to study the emissions from nascent and aged plumes from the African savannah and the tropical forests of Amazonia in Brazil during the TROFFEE campaign during the 2004 dry season (Yokelson et al, 2007b); but given the highly variable emissions inherent to biomass burning, particularly between lofted and unlofted emissions, even from within a single fire type Burling et al, 2011), it is uncertain whether this type of detailed characterization can be carried out with space-borne measurements and has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%